Investigating the variability in pressure–volume relationships during hemorrhage and aortic occlusion - Mobin, Fahim Usshihab; Renaldo, Antonio C.; Carrasco Perez, Enrique; Jordan, James E.; Neff, Lucas P.; Williams, Timothy K.; Johnson, M. Austin; Rahbar, Elaheh (Frontiers in Cardiovascular Medicine, 2023)
Left ventricle pressure-volume (P-V) relationships are the classical benchmark for studying cardiac mechanics and pumping function. Perturbations in the P-V relationship (or P-V loop) can be informative and guide the management of heart failure, hypovolemia, and aortic occlusion. Traditionally, P-V loop analyses have been limited to a single beat P-V loop or an average of consecutive P-V loops and there are limited tools to evaluate the variations in P-V relationships longitudinally over time. This is particularly important when studying acute and transient hemodynamic and cardiac events, such as active hemorrhage or aortic occlusion. In this study, we aimed to investigate the variability in P-V relationships during hemorrhagic shock and aortic occlusion, by leveraging on a previously published porcine hemorrhage model. Briefly, swine were instrumented with a P-V catheter in the left ventricle of the heart and underwent 25% total blood volume hemorrhage over 30 minutes, followed by either Zone 1 complete aortic occlusion (i.e., REBOA), Zone 1 endovascular variable aortic control (EVAC), or no occlusion, as a control, for 45 minutes. Preload-independent metrics of cardiac performance were obtained at predetermined time points by performing inferior vena cava occlusion (IVCO) during a ventilatory pause. Continuous P-V loop data, and other hemodynamic flow and pressure measurements were collected in real-time using a multi-channel data acquisition system. We developed a custom algorithm to quantify the time-dependent variance in both load-dependent and independent cardiac parameters from each P-V loop. As expected, all pigs displayed a significant decrease in end-systolic pressures and volumes, after hemorrhage. The variability in response to hemorrhage was consistent across all three groups. However, upon introduction of REBOA, we observed significantly high levels of variability in both load-dependent and independent cardiac metrics such as ESP, ESV, and elastance. For instance, pigs receiving REBOA experienced a 342% increase in ESP from hemorrhage, while pigs receiving EVAC experienced only 188% increase. The level of variability within the EVAC group was consistently less than the REBOA group, which suggests that the EVAC group may be more supportive of maintaining healthier cardiac performance than complete occlusion with REBOA.